2023
DOI: 10.1212/nxi.0000000000200084
|View full text |Cite
|
Sign up to set email alerts
|

Ocrelizumab Impairs the Phenotype and Function of Memory CD8 + T Cells

Abstract: Background and ObjectiveDepleting CD20+B cells is the primary mechanism by which ocrelizumab (OCRE) is efficient in persons with multiple sclerosis (pwMS). However, the exact role of OCRE on other immune cell subsets directly or indirectly remains elusive. The purpose of this study is to characterize the dynamics of peripheral immune cells of pwMS on OCRE.MethodsWe collected blood samples from 38 pwMS before OCRE onset (T0) and at 6 and 12 months (T6, T12) after initiation. To cover the immune cell diversity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“… 58 Another recent study demonstrated subtle modifications within the CD8 + T cell population in patients undergoing BCDT treatment. 59 Considering that B cell depletion effectively removes 5%–10% lymphocytes from the PBMC compartment, the subtlety of the consequences for the remaining immune compartment is rather surprising. When considering genetic variations while examining monozygotic twin pairs discordant for MS, minimal disparities were detected in the frequencies of canonical leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“… 58 Another recent study demonstrated subtle modifications within the CD8 + T cell population in patients undergoing BCDT treatment. 59 Considering that B cell depletion effectively removes 5%–10% lymphocytes from the PBMC compartment, the subtlety of the consequences for the remaining immune compartment is rather surprising. When considering genetic variations while examining monozygotic twin pairs discordant for MS, minimal disparities were detected in the frequencies of canonical leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has also demonstrated an effect of anti-CD20 antibody treatment in T-cell response, which may in part account for this observation. 30 In addition, B-cell depletion has been hypothesized to affect the latent EBV virus contained within the B-cell compartment. 31 The low cellular response to EBNA-1 with anti-CD20 antibodies did not result in a corresponding decrease in EBNA-1 IgG levels—as seen in a previous longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Mathias et al, demonstrated a depletion in memory CD8+CD20+ T cells post OCR. Although JCV specific cell immune responses were not studied, one can extrapolate a similar response [12].…”
Section: Discussionmentioning
confidence: 99%